Realizing the potential of plant genetic resources: the use of phenomics for genebanks - Ghamkhar, Kioumars; Hay, Fiona; Engbers, Marleen; Dempewolf, Hannes; Schurr, Ulrich (Wiley, 2025)
Societal Impact Statement Genebanks contribute to global food security, directly influencing societal well-being, by providing access to seed or genetic material that is more resilient to pests, diseases, and environmental stresses. The ability to develop crops adapted to changing environmental conditions and with high nutritional value means societies can better cope with the adverse effects of climate change, safeguarding food production and rural livelihoods. Enhancing sustainable crop traits, such as improved water-use efficiency and nutrient utilization, supports the transition toward more sustainable agricultural practices. New technologically advanced phenotyping tools are required to optimally realize the potential of these genetic resources, to identify plant genetic resources that will best enable us to address current global challenges.